2019
DOI: 10.1371/journal.pone.0215782
|View full text |Cite
|
Sign up to set email alerts
|

The Quansys multiplex immunoassay for serum ferritin, C-reactive protein, and α-1-acid glycoprotein showed good comparability with reference-type assays but not for soluble transferrin receptor and retinol-binding protein

Abstract: The Quansys multiplex (Q-Plex) measures ferritin (Fer), soluble transferrin receptor (sTfR), C-reactive protein (CRP), α-1-acid glycoprotein (AGP), and retinol-binding protein (RBP). We compared Q-Plex results with reference-type assays and evaluated Q-Plex performance. Pearson correlation and Lin’s concordance coefficients between the Q-Plex and reference assay were: Fer 0.98 and 0.91, sTfR 0.88 and 0.35, CRP 0.98 and 0.98, AGP 0.82 and 0.81, and RBP 0.68 and 0.31, respectively. The median relative difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The strength of this study was the assessment of iron status by measuring two different biomarkers (ferritin and sTfR) using a validated method [29]. However, we do acknowledge that a recent study comparing the Quansys multiplex immunoassay with reference-type assays found poor precision for sTfR in comparison with the Roche cobas 6000 clinical analyser [41]. Nonetheless, the Hb threshold that we obtained by ROC curve analysis for the detection of ID (based on ferritin) was identical to the one for the detection of IDE (based on sTfR), although the latter mainly served as sensitivity analysis.…”
Section: Discussionmentioning
confidence: 98%
“…The strength of this study was the assessment of iron status by measuring two different biomarkers (ferritin and sTfR) using a validated method [29]. However, we do acknowledge that a recent study comparing the Quansys multiplex immunoassay with reference-type assays found poor precision for sTfR in comparison with the Roche cobas 6000 clinical analyser [41]. Nonetheless, the Hb threshold that we obtained by ROC curve analysis for the detection of ID (based on ferritin) was identical to the one for the detection of IDE (based on sTfR), although the latter mainly served as sensitivity analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Work is ongoing to improve the performance of the 7-Plex assay and includes improvements to ferritin, RBP4, and sTfR assays. A challenge inherent to multiplex assay methods is simultaneously optimizing the assay performance for both high-and low-abundant proteins; forthcoming improvements to assay sensitivity for ferritin will allow for a change to the recommended sample dilution from 1:10 to 1:40, a change that is expected to improve precision for RBP4 assay values by bringing them closer to the middle of the reportable assay range, a previous criticism of the 7-plex [27,28]. Similarly, changes to the sTfR assay to improve precision are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratories at PATH, the University of Washington, Quansys, and UC Davis had previously collaborated to develop and verify the performance of the Human Micronutrient assay [22][23][24] (Fig 1). Other laboratories, including ones from the US Centers for Disease Control and Prevention (CDC, GA), Eurofins Craft Technologies, Inc. (NC), Binghamton University (SUNY), and the University of British Columbia have also been independently evaluating the performance of the Human Micronutrient assay [27][28][29][30]. Once each laboratory had signed the MTA to access the samples, two complete sets of 76 heparin plasma samples and two of the G and H quality control sets, were shipped on dry ice via overnight courier.…”
Section: Construction Of Blinded Test Panelsmentioning
confidence: 99%
“…For the determination of each analyte concentration corresponding protein standards are applied [26,27]. Commercially available planarbased multiplex ELISA kits, requiring chemiluminescent detection for quantification of inflammatory markers in serum, plasma, urine, cell, and tissue lysate from different sources have also been produced [28]. Additionally, chemiluminescence-based single molecular analysis arrays are produced enabling performance of up to a 12-plex assay in a well [26].…”
Section: Chemiluminescencementioning
confidence: 99%